2021
DOI: 10.1111/jnu.12711
|View full text |Cite
|
Sign up to set email alerts
|

Analytics and Lean Health Care to Address Nurse Care Management Challenges for Inpatients in Emerging Economies

Abstract: Purpose: Prescriptive and predictive analytics and artificial intelligence (AI) provide tools to analyze data with objectivity. In this paper, we provide an overview of how these techniques can improve nursing care, and we detail a quantitative model to afford managerial insights about care management in a Hospital in Colombia. Our main purpose is to provide tools to improve key performance indicators for the care management of inpatients which includes the nurse workload. Methods: The optimal nurse-to-patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…Proces digitization allows for better management of resources (20). Our study predicts that a replacement of paper-based documentation systems with COPE and CDSSsupported CLMA systems in the PDC will prevent unnecessary production, movement, transportation, and error waste in the process.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Proces digitization allows for better management of resources (20). Our study predicts that a replacement of paper-based documentation systems with COPE and CDSSsupported CLMA systems in the PDC will prevent unnecessary production, movement, transportation, and error waste in the process.…”
Section: Discussionmentioning
confidence: 91%
“…Davies et al (3) analyzed nurse processes by the lean approach and reported that nurses spent more time at the desk rather than bedside visits, made repetitive data entries, spent excessive time on drug preparation and orders, and therefore, allocated less time for direct patient care. Studies of digitalization processes show that digital systems save nurses' time, facilitate care processes, reduce the time allocated to desk work, prevent double entries by eliminating the use of both paper and digital systems, and reduce the time nurses spend preparing paper documents, medication prescriptions, and drug orders (19)(20)(21)(22). In addition, digitalized applications improve nursing practices by allowing them to use a computerized doctor order entry system, have warning screens for confirming patient identity and drug names/appearance, and prevent handwriting errors, thus increasing the quality of recording systems and preventing errors (7,(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Veena and Aravindhar (2021) used machine learning techniques to design a remote monitoring system for prenatal risk detection that allows healthcare providers to connect with pregnant women for remote supervision and consultation effectiveness. Moreover, Moreno-Fergusson et al (2021) illustrated the use of an AI approach to analyse healthcare data; the generated rules were then employed in nurse care management for inpatients. In addition, some scholars developed AI-based predictive models through machine learning methods to identify patients at high risk of falls.…”
Section: Resultsmentioning
confidence: 99%
“…West and West (2000) used an AI‐based medical diagnostic system for breast cancer detection. Recently, Moreno‐Fergusson et al (2021) stated that conducting AI prescriptive and predictive analytics improves inpatient care management and reduces nurse workload. Zhou et al (2022) applied an AI standardized electronic handover system that has great potential for improving paediatric patient safety and the quality of handovers.…”
Section: Introductionmentioning
confidence: 99%
“…Ejemplo de seguimiento empleando los indicadores: cambio de turno de enfermería Fuente: Elaboración propia Indicadores de cuidado de enfermería hospitalario orientados por modelo de práctica profesional económicos. Podría sugerirse complementar estos indicadores bajo el método lean healthcare, para garantizar su mayor eficiencia (28,29,30).…”
Section: Discussionunclassified